Amazonki - mit czy reminiscencja zwyczajów koczowników - Janik, Paweł (Studia Azjatystyczne, 2017)
There is evidence (archaeological, historical, linguistic, iconographic, ethnological and other mentioned in this article) to show that the formation of the myth of the Amazons could be a result of observations of habits of Iranian nomads who used to live in the areas of the northern coast of the Black Sea and Central Asia in Antiquity. Some datum indicates that women from these communities (as in many other groups of nomads) had a much higher social status than in many settled communities such as the ancient Greeks and Romans. Women in the Iranianspeaking nomadic communities were likely to participate in hunting and, to some limited extent, in fighting. In addition, some of them might have become the heads o f these groups as queens (that is not as wives of kings but as independent rulers). All o f it influenced the imagination of people from Greek culture who had met the nomads. Stories about these warrior women spread into Greek ecumene, increasingly evolving and subject to distortion, thus affecting the myth of the Amazons. The Amazons in Greek mythology and art often have nomadic features - they ride on horseback, wear bows and “Scythian” costumes and weapons. Tales of warlike women did not only contribute to the mythology of the ancient world, but they were inherited by Turkic-speaking groups and are still present in the culture of Iran.